Pediatric simulation in undergraduate nursing education: A Scoping Review - Evans Appiah-Kusi; Tracy M. Christianson (Elsevier, 2024)
Background: The use of simulation in nursing education continues to grow. However, the evidence available in the field of pediatric simulation is not robust. Since studies have reported how simulation impacts nursing students learning, it is vital to fully understand pediatric simulation on undergraduate nursing students' learning. Aim: This scoping review aimed to uncover the breadth of pediatric simulation use in undergraduate nursing education programs. Method: This review identified current studies of pediatric simulations in undergraduate nursing students through a scoping review using the framework proposed by Arksey and O'Malley (2005). The studies reviewed were found through CINAHL, Medline, PubMed, and Google Scholar. Each study was analyzed, and data charted. A total of 23 studies met the inclusion criteria and were included in this scoping review. Results: Students showed improved self-confidence scores, knowledge, clinical judgement, skills, and self-reported satisfaction with pediatric simulation-based learning. Conclusion: Incorporating pediatric simulation in undergraduate nursing programs will help improve students' knowledge, confidence, clinical judgement, and nursing skills.